2003
DOI: 10.1046/j.1460-9568.2003.02851.x
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory cortical responses during the expectancy of a predictable painful stimulation. A high‐resolution electroencephalography study

Abstract: In the present study, high-resolution electroencephalography techniques modelled the spatiotemporal pattern of human anticipatory cortical responses preceding expected galvanic painful stimuli (non-painful stimuli as a control). Do these responses reflect the activation of associative other than somatosensory systems? Anticipatory processes were probed by alpha oscillations (6-12 Hz) for the evaluation of thalamocortical channels and by negative event-related potentials for the evaluation of cortical excitabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
67
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 55 publications
10
67
0
Order By: Relevance
“…Previous studies on prestimulus alpha activity and detection ability have yielded inconsistent results (Babiloni et al, 2003;Ergenoglu et al, 2004). One explanation for the discrepancies might stem from the fact that several sources in the human brain produce oscillatory activity in the alpha band (Hari and Salmelin, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on prestimulus alpha activity and detection ability have yielded inconsistent results (Babiloni et al, 2003;Ergenoglu et al, 2004). One explanation for the discrepancies might stem from the fact that several sources in the human brain produce oscillatory activity in the alpha band (Hari and Salmelin, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Both studies, however, did not investigate possible pre-stimulus effects of attention. Previous work addressing pre-stimulus effects showed that anticipation of a painful stimulus already results in a suppression of alpha activity (Babiloni et al, 2003(Babiloni et al, , 2004Del Percio et al, 2006). This anticipatory suppression is again stronger for a painful compared to a non-painful stimulus (Babiloni et al, 2003) and less prominent, if the subject is distracted by mentally performing an arithmetical task .…”
Section: Introductionmentioning
confidence: 91%
“…Thus, for instance, lowered power in the alpha rhythm over primary somatosensory cortex has been observed during the expectancy of predictable painful stimulation (Babiloni et al, 2003(Babiloni et al, , 2006. Early reports have also revealed that chronic pain patients show less alpha asymmetry than healthy subjects (De Benedittis and De Gonda, 1985;Stevens et al, 2000), and that neurofeedback training to increase alpha waves would be an effective method to reduce pain perception (Melzack and Perry, 1975).…”
Section: Introductionmentioning
confidence: 99%